The Effect of Using Quizlet Toward Students’ Vocabulary Mastery - Sri Utami Dewi; Sayida Rahma (STKIP PGRI Trenggalek, 2022)
The aim of this research was to know if there is significant effect of using Quizlet toward student vocabulary mastery. This research was using quasi-experimental research with two types of variable. First variable was the application of Quizlet as the independent variable while the second variable was the vocabulary mastery as the dependent variable. The samples in this research are students of eleventh grade at SMA Negeri 2 Trenggalek they were MIPA 2 as experimental group and MIPA 5 as control group. The experimental group was using Quizlet as learning media while the control group was not. The instrument was to collect the data of this research by pre-test and post-test. After the data was collected, the researcher analyzed the data by using independent sample t-test. Based on test the Sig. (2-tailed) of post-test were 0.000 <0.05, than as the basic rules of making independent sample t-test, it can be concluded that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant difference between the average student learning outcomes in the experimental group and the control group. So, Quizlet application is an effective learning media for students' vocabulary mastery